qNMR in natural products: practical approaches. What nobody tells you before starting your qNMR study! - Ravaglia, Luciana Marcal; de Oliveira, Paola Dias; Holzgrabe, Ulrike; Alcantara, Glaucia Braz (Frontiers in Natural Products, 2024)
NMR (nuclear magnetic resonance) spectroscopy is a well-established technique for elucidating the structure and composition of Natural Products (NP). However, while NMR spectra offer qualitative insights, there is often a growing demand within the NP research community for quantitative analysis using NMR techniques. Unfortunately, this demand is sometimes met with misconceptions and lacks the methodological rigor typically associated with analytical procedures, particularly concerning validation and mandatory adjustments of quantitative NMR (qNMR) parameters. Therefore, this minireview highlights the practical approaches concerning preparation and validation for qNMR analyses of plant extracts. Specifically, we provide a concise protocol detailing experimental settings crucial for ensuring the accuracy and reliability of quantitative measurements. It is noteworthy that such guidance is often absent in existing literature, and our minireview wants to bridge this gap by offering clear methodological recommendations.